Pengembangan Pariwisata Pantai Merta Sari Sanur Melalui Pemasaran Digital dengan Konsep Tri Hita Karana untuk Mendukung Eco Tourism di Bali - I Komang Sumerta; I Wayan Meryawan; Tjokorda Gde Agung Wijaya Kesuma Suryawa; I Gusti Putu Agung Widyagoca; I Kadek Dwi Diatmika (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to develop environment-based local tourism destinations through digital marketing with the Tri Hita Karana concept to support Eco Tourism in Bali. This service method uses education, training, mentoring, evaluation and sustainability. The results of this service show that digital-based tourism marketing is able to provide awareness to the wider community, especially domestic and international tourists about the existence and facilities of tourist objects owned by Mertasari Beach. This tourist awareness will be able to increase the level of tourist visits to Mertasari Beach so that the economy of the surrounding community can also increase. Of course, the increase in tourist visits cannot be separated from tourism objects that must always provide a comfortable, clean and beautiful atmosphere in line with the Palemahan concept in Tri Hita Karana.